Phosphorus and nitrogen losses in relation to forest, pasture and row-crop land use and precipitation distribution in the midwest usa - Udawatta, Ranjith; Henderson, Gray; Jones, John; Hammer, David (Revue des sciences de l’eau / Journal of Water Science, 2011)
Little information is available comparing the influence of land use and precipitation on the control of phosphorus (P) and nitrogen (N) losses from agricultural watersheds in claypan soils. Eight watersheds with varying proportions of row-crop, pasture, forest, and grass filter strip condition were examined for three consecutive years to evaluate effects of land use and precipitation on P and N losses from row-cropped watersheds. Total P (TP) and total N (TN) losses were inversely related to the percentage of forest and pasture cover. Forest (n=2), pasture (n=3), row-crop (n=2), and row-crop grass filter strip (n=1) land use types had mean annual TP losses of 0.43, 0.90, 3.82 and 1.30 kg•ha-1•yr-1, respectively and mean annual TN losses of 2.02, 4.34, 29.25 and 12.31 kg•ha-1•yr-1, respectively. During the 3-year study, the respective land use types lost 0.36, 0.64, 13.99 and 7.26 kg NO3-N•ha-1•yr-1. Runoff events on row-cropped watersheds resulted in significantly greater TP, TN, and NO3-N losses than those from pastured and forested watersheds. Stream nitrate-N concentrations averaged 0.39, 0.50, and 2.56 mg•L-1 for forest, pasture, and row-crop land use types, respectively. During the study, 136% of the long-term average precipitation in 1998 caused significant nutrient losses in all watershed categories and the variability within a land use type was larger than in years with below long-term rainfall. The study results emphasize the incorporation of perennial vegetation such as vegetative buffers, grass/conservation reserve program areas, and grass filter strips or other perennial vegetation as a long-term option for effective control of nutrient losses in runoff from agricultural watersheds.